Macro-propagation of Paulownia fortunei (Seem.) Hemsl., an Agroforestry Tree from China - Kumar, Lalit; Mangat, P.S.; Dhanda, R.S. (Indian Journal of Agroforestry, 2020)
Paulownia fortunei (Seem.) Hemsl., an ideal agroforestry tree in China, has been introduced as an alternative to Poplars in Punjab state. Standardization of propagation technology is a pre-requisite for successful introduction, demonstration and adoption by the farmers. Vegetative propagation of P fortunei through macro-propagation was studied during 1999- 2000 and 2002-03 at the PAU, Ludhiana. It was studied through nine root-cutting sizes (three thicknesses and three lengths) during 1999-2000. Thicker root cuttings of medium length (3 cm x 15 cm) performed best and produced the nursery plants with thicker collar diameter (8.4 cm), plant height (6.8 m) and diameter at breast height (6.0 cm), whereas longer root cuttings (20 cm) produced equally tall plants (6.7 m). During 2002-03, root cuttings of six combinations of two lengths (15 and 20 cm) and three thicknesses (1, 2 and 3 cm) were tried in two environments (polybags and nursery beds). Longer and thicker root cuttings (20x3cm) gave the best performance for all growth parameters (CD, DBH and plant height) in polybags, whereas the root cuttings of 20x3 cm size in nursery beds performed best for CD (2.3cm) and DBH (2.1 cm), while 20x2 cm root cuttings gave best results for plant height in nursery stock.